John Stuart Mill's Philosophy of Persuasion - Helen Ruth McCabe (Informal Logic, 2014)
In his youth, John Stuart Mill followed his father’s philosophy of persuasion but, in 1830, Mill adopted a new philosophy of persuasion, trying to lead people incrementally towards the truth from their original stand-points rather than engage them antagonistically. Understanding this change helps us understand apparent contradictions in Mill’s cannon, as he disguises some of his more radical ideas in order to bring his audience to re-assess and authentically change their opinions. It also suggests a way of re-assessing the relationship between Mill’s public and private works, to which we should look if we are attempting to understand his thought.